The linguistic dating of the Joseph Story - Joosten, J (Mohr Siebeck, 2019)
Establishing a probable date for the Joseph story has proven difficult, and until the present day widely divergent temporal horizons continue to be proposed. An approach based on historical linguistics promises to narrow down the window of probability. Like all human languages, Biblical Hebrew changed over time in ways that can be tracked and recorded. The present paper proposes a detailed analysis of the language of the Joseph story in diachronic perspective.